2007
DOI: 10.1016/j.addr.2007.08.017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pharmaceutical excipients on drug disposition

Abstract: Many new chemical entities are poorly soluble, requiring the use of co-solvents or excipients to produce suitable intravenous formulations for early pre-clinical development studies. There is some evidence in the literature that these formulation components can have significant physiological and physicochemical effects which may alter the distribution and elimination of co-administered drugs. Such effects have the potential to influence the results of pre-clinical pharmacokinetic studies, giving a false impres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 125 publications
1
52
0
4
Order By: Relevance
“…P-gp activity is modulated by the physical state of lipid bilayer where the protein actually resides. Several pharmaceutical agents of natural or synthetic origin that belong to various categories like the cosolvents, surfactants, polymer and lipid excipients were identified to have the P-gp inhibitory action (Buggins, Dickinson, Taylor, 2007). The mechanism of action differs with the type of excipient as presented in Table III (Bansal et al, 2009a).…”
Section: Pharmaceutical Excipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…P-gp activity is modulated by the physical state of lipid bilayer where the protein actually resides. Several pharmaceutical agents of natural or synthetic origin that belong to various categories like the cosolvents, surfactants, polymer and lipid excipients were identified to have the P-gp inhibitory action (Buggins, Dickinson, Taylor, 2007). The mechanism of action differs with the type of excipient as presented in Table III (Bansal et al, 2009a).…”
Section: Pharmaceutical Excipientsmentioning
confidence: 99%
“…Excipients are safe, not absorbed from the intestine or gut and have wide pharmaceutical acceptance with a fair history of being incorporated into the parenteral and external formulations as solubilizing and stabilizing agents (Buggins, Dickinson, Taylor, 2007). Besides, in the present scenario, there is increasing development of novel drug delivery systems (DDS) like microspheres, nanoparticles and liposomes, all of which have inherent P-gp evading activity (Kim, Lim, 2002).…”
Section: Pharmaceutical Formulationsmentioning
confidence: 99%
“…(Lo, 2000; Wandel, Kim, Stein, 2013) Excipients are material used in drug formulations alongside the active compound. They were believed to be an inactive part of a drug formulation; however, studies demonstrated that excipients are not inert and they can have subtle effects on absorption or elimination of concomitant drugs administered (Buggins, Dickinson, Taylor, 2007). Many attempts have been made to evaluate the capability of excipients to augment drug BA.…”
mentioning
confidence: 99%
“…In most cases, the formulation strategies require the use of various solvents and/or excipients during the production step. These excipients have to be approved or recognized as "generally recognized as safe" (GRAS) substances for pulmonary drug delivery [40,[44][45]. Moreover, the residual solvents have to be below some acceptable limits [46].…”
Section: Pulmonary Drug Deliverymentioning
confidence: 99%